The behavior of foreign professors at the Federal University of Ceará within the scope of career self-management (Research, Society and Development, 2021)
The objective of this work is to identify and analyze the behaviors of foreign professors from Federal University of Ceará in relation to careers self-management, considering King's theoretical model of self-management of career (2004), the types of Behavior of Positioning, Influence and Boundary Management (work-life limits) of these professors were characterized. This research had a qualitative, interpretative approach, carried out through semi-structured interviews with 13 effective foreign professors working at Federal University of Ceará. In relation to the primary data, these were treated through content analysis, using Atlas TI software. The results pointed out that their prevailing Positioning Behavior refers to the innovation of the content of the work; the main Behaviors of Influence adopted by them are self-promotion and ascendant influence; and the Management of Work-Life Limits is managed satisfactorily by foreign professors at the Federal University of Ceará.